2002
DOI: 10.1097/01.ico.0000263122.45898.09
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Histopathology of Human Meibomian Gland

Abstract: Various histopathologic changes were observed in the human meibomian gland. Hyperkeratinization of ductal epithelium and atrophy of acinar cells may cause meibomian gland dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 5 publications
8
100
0
4
Order By: Relevance
“…The age-related changes observed were consistent with histopathologic changes noted by Obata et al in humans, which showed atrophy of the acini (Obata, 2002). More recently, atrophy of the mouse MG was demonstrated by measuring the cross-sectional area of the gland (Nien et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The age-related changes observed were consistent with histopathologic changes noted by Obata et al in humans, which showed atrophy of the acini (Obata, 2002). More recently, atrophy of the mouse MG was demonstrated by measuring the cross-sectional area of the gland (Nien et al, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…A number of changes occur in the human MG with age that are thought to account for the increased frequency of meibomian gland dysfunction (MGD) in older populations (Hom et al, 1990;Mathers et al, 1991;Mathers and Lane, 1998) including MG "dropout," orifice plugging, cystic dilation of the duct, and atrophy of the MG acini (Gutgesell et al, 1982;Robin et al, 1985;Hykin and Bron, 1992;Mathers, 1993;Obata et al, 1994;Obata, 2002). These structural changes are thought to lead to altered or reduced tear outflow leading to disruption of the tear film, increased tear evaporation, and increased tear osmolarity that cause ocular discomfort, eye irritation, and chronic blepharitis.…”
Section: Introductionmentioning
confidence: 99%
“…The expression and production of PLA 2 in the cornea ( 6 ), conjunctiva, and lacrimal glands ( 37 ) has been well documented. In fact, the ocular epithelial tissues could be regarded as a continuum, and the lacrimal gland and meibomian gland simply denote invaginations of this continuous epithelium ( 38 ). Swartz and colleagues ( 39 ) have previously shown that mechanical stress could be communicated between different cell types to bring about comprehensive matrix remodeling in the airway system.…”
Section: Meibum-derived Amphiphilic Lipids In Maintaining Tear Fi Lm mentioning
confidence: 99%
“…Alternatively, the ectopic epithelial cells might arise as a result of hyperkeratinization of differentiating acinar cells due to the reduction in FATP4. Defective acinar cells and hyperkeratinization of ductal epithelial cells are two major areas of pathogenesis of meibomian gland dysfunction in humans (38). Our Fatp4 Ϫ/Ϫ ;Tg(IVL-Fatp4) mice could be a useful mouse model for elucidating the pathogenesis and identifying potential therapies for meibomian gland dysfunction.…”
Section: Fatp4mentioning
confidence: 99%